2015
DOI: 10.4254/wjh.v7.i4.703
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment prediction of response to peginterferon plus ribavirin in chronic hepatitis C genotype 3

Abstract: AIM:To evaluate pre-treatment factors associated with sustained virological response (SVR) in patients with hepatitis C virus (HCV) genotype 3 treated with peginterferon and ribavirin (RBV). (62/107) of the patients achieved an SVR and 42% (45/107) did not. In the multivariate logistic regression analysis, pre-treatment HCV-RNA ≥ 600000 UI/mL (OR = 0.375, 95%CI: 0.153-0.919, P = 0.032) and advanced fibrosis (OR = 0.278, 95%CI: 0.113-0.684, P = 0.005) were significantly associated with low SVR rates. In patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…This is in line with Rizk et al10 who obtained SVR in 45.5% of Egyptian patients with HCV, genotype 4. Higher levels of SVR (58%) were reported in patients with genotype 39 and lower levels (36%) were observed in patients genotype 18 . These data support the conclusion of Jang and Chung32 that genotype 1 responds weakly to treatment, while genotype 3 responds better.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is in line with Rizk et al10 who obtained SVR in 45.5% of Egyptian patients with HCV, genotype 4. Higher levels of SVR (58%) were reported in patients with genotype 39 and lower levels (36%) were observed in patients genotype 18 . These data support the conclusion of Jang and Chung32 that genotype 1 responds weakly to treatment, while genotype 3 responds better.…”
Section: Discussionmentioning
confidence: 90%
“…Viral load was evaluated as a predictive factor by some studies with controversial results810 . The stage of liver fibrosis was claimed to be a good predictor of treatment response in HCV infection9,11. However, this claim could not be supported by others8,10,12 Last but not least, was the genotyping of IL-28 B which has been reported to be a strong predictor of treatment outcome in HCV patients10,13–15.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies showed that predisposition for the HCV relapse is related to female gender, older age, high body mass index (BMI), high viral load before treatment, HCV genotype 1, HCV molecular characteristics (especially HCV core region), genetic predisposition of patients (ILB28), previous therapy with IFN and also cumulative dose of administered drugs, ribavirin, as most important [16][17][18] . Despite the statistical irrelevance, due to a small number of patients in addition to CHC, all three patients had some autoimmune disease in common -the patient No.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic HCV, the presence of steatosis can predict treatment failure (in the cases of pegylated interferon and ribavirin) [ 19 , 20 ]. Compared with other predictors of treatment failure in HCV, such as genotype, viral load and ethnicity, the relationship between steatosis and treatment failure is less well understood.…”
Section: Steatosismentioning
confidence: 99%